PENGARUH MODEL PEMBELAJARAN STAD TERHADAP HASIL BELAJAR PKN SISWA KELAS V DI SDN 04 BENGKAYANG - Robin; Margaretha Lidya Sumarni (STKIP Subang, 2025)
This study aims to determine the effect of the cooperative learning model type STAD (Student Teams Achievement Division) on the Civics Education (PKN) learning outcomes of fifth-grade students at SDN 04 Bengkayang. The research employed an experimental method with a quantitative approach. The subjects consisted of two groups: an experimental class taught using the STAD model and a control class taught with conventional methods. Data collection techniques included observation and multiple-choice tests, and the data analysis involved normality tests, homogeneity tests, t-tests, and effect size calculation using SPSS version 22. The findings revealed that the STAD learning model significantly improved students' learning outcomes in Civics Education. The significance value (2-tailed) was 0.001 (< 0.05), with an effect size of 0.31, categorized as moderate. Therefore, it can be concluded that the application of the STAD model is effective in enhancing students' Civics learning outcomes and promoting active participation in the classroom.